+0

# [Veteran - member] Need help with a der. rule

0
63
1

I need a quick refresher for this, i have in 4 hours and would like to see the rules in action in a simple problem like this.

Guest Nov 14, 2017
Sort:

#1
0

Find the derivative of the following via implicit differentiation:
d/dy(g(y)) = d/dy(16 (1/y - sqrt(y) + 2 y^3))

The derivative of g(y) is g'(y):
g'(y) = d/dy(16 (1/y - sqrt(y) + 2 y^3))

Factor out constants:
g'(y) = 16 d/dy(1/y - sqrt(y) + 2 y^3)

Differentiate the sum term by term and factor out constants:
g'(y) = 16 d/dy(1/y) - d/dy(sqrt(y)) + 2 d/dy(y^3)

Use the power rule, d/dy(y^n) = n y^(n - 1), where n = -1: d/dy(1/y) = d/dy(y^(-1)) = -y^(-2):
g'(y) = 16 (-(d/dy(sqrt(y))) + 2 (d/dy(y^3)) + (-1)/(y^2))

Use the power rule, d/dy(y^n) = n y^(n - 1), where n = 1/2: d/dy(sqrt(y)) = d/dy(y^(1/2)) = y^(-1/2)/2:
g'(y) = 16 (-1/y^2 + 2 (d/dy(y^3)) - 1/(2 sqrt(y)))

Use the power rule, d/dy(y^n) = n y^(n - 1), where n = 3: d/dy(y^3) = 3 y^2:
g'(y) = 16 (-1/y^2 - 1/(2 sqrt(y)) + 2 3 y^2)

Simplify the expression:
g'(y) = 16 (-1/y^2 - 1/(2 sqrt(y)) + 6 y^2) - Courtesy of "Mathematica 11 Home Edition"

Guest Nov 14, 2017

### 12 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details